3D chest tomosynthesis using a stationary flat panel source array and a stationary detector: a Monte Carlo proof of concept. (18th November 2021) - Primidis, Thomas G; Wells, Stephen G; Soloviev, Vadim Y; Welsch, Carsten P
Abstract: 3D imaging modalities such as computed tomography and digital tomosynthesis typically scan the patient from different angles with a lengthy mechanical movement of a single x-ray tube. Therefore, millions of 3D scans per year require expensive mechanisms to support a heavy x-ray source and have to compensate for machine vibrations and patient movements. However, recent developments in cold-cathode field emission technology allow the creation of compact, stationary arrays of emitters. Adaptix Ltd has developed a novel, low-cost, square array of such emitters and demonstrated 3D digital tomosynthesis of human extremities and small animals. The use of cold-cathode field emitters also makes the system compact and lightweight. This paper presents Monte Carlo simulations of a concept upgrade of the Adaptix system from the current 60 kVp to 90 kVp and 120 kVp which are better suited for chest imaging. Between 90 kVp and 120 kVp, 3D image quality appears insensitive to voltage and at 90 kVp the photon yield is reduced by 40%–50% while effective dose declines by 14%. A square array of emitters can adequately illuminate a subject for tomosynthesis from a shorter source-to-image distance, thereby reducing the required input power, and offsetting the 28%–50% more input power that is required for operation at 90 kVp. This modelling suggests that lightweight, stationary cold-cathode x-ray source arrays could be used for chest tomosynthesis at a lower voltage, with less dose and without sacrificing image quality. This will reduce weight, size and cost, enabling 3D imaging to be brought to the bedside.